Bayesian network meta-comparison of maintenance treatments for stage IIIb/IV non-small-cell lung cancer (NSCLC) patients with good performance status not progressing after first-line induction chemotherapy: Results by performance status, EGFR mutation, histology and response to previous induction. Issue 16 (November 2015) - Tan, Pui San; Lopes, Gilberto; Acharyya, Sanchalika; Bilger, Marcel; Haaland, Benjamin
Abstract Background Recent trials have suggested that maintenance treatments improve outcomes for patients not progressing after first-line therapy for advanced non-small-cell lung cancer (NSCLC). However, physicians have little guidance on selecting which patients benefit the most and what drug or regimen is optimal. Here, we report a systematic review and network meta-analysis of maintenance treatments in subgroups determined by performance status (PS), epidermal growth factor receptor (EGFR) mutation, histology and response to induction. Methods PubMed and conference proceedings were reviewed and individual study relative efficacy measures were meta-analysed in a Bayesian hierarchical model. The primary outcome, overall survival (OS), was evaluated in terms of (i) posterior surface under cumulative ranking curve (SUCRA), (ii) probability of being best treatment, (iii) probability of outperforming no maintenance, and (iv) posterior median hazard ratio (95% credible interval). Secondary outcomes were progression-free survival (PFS) and adverse events. Findings Twelve trials evaluating eight maintenance treatments in 3850 patients were meta-analysed. Selected maintenance treatments showed clinically meaningful benefits of ⩾20% reduction in hazards of death with ⩾90% probability of outperforming no maintenance in terms of OS: (i) switch to or continue pemetrexed (nonsquamous), continue gemcitabine, or switch to EGFR tyrosine kinase inhibitors (TKIs) for PS 0 patients, (ii) switch to pemetrexed (nonsquamous) for PS 1 patients, (iii) switch to EGFR TKI for EGFR mutation positive patients, (iv) switch to or continue pemetrexed or switch to EGFR TKI for nonsquamous patients, (v) continue gemcitabine for squamous patients, (vi) switch to docetaxel or continue gemcitabine for responders to induction, or (vii) switch to or continue pemetrexed (nonsquamous) or switch to EGFR TKI for patients with stable disease post-induction. Interpretation Maintenance treatments show clinically meaningful survival benefits in good performance status patients with advanced NSCLC not progressing after first-line chemotherapy. Benefits are optimised by targeting specific maintenance to individual patients guided by PS, EGFR mutation status, histology and response to induction.